Caracterização e avaliação da atividade fotodinâmica de tetra-meso-[(piridil)porfirina]platina(II) frente à microorganismos - Acunha, Thiago Vargas (2017)
This work deals with the synthesis of Tetra-meso-[(3-pyridyl)-chloro-2,2'-bipyridyl-platinum(II)]porphyrin (3-H2TPtPyP) and Tetra-meso-[(4-pyridyl)-chloro-2,2'-bipyridyl-platinum(II)]porphyrin (4-H2TPtPyP), starting from their respective precursors Tetra-meso-[(3-pyridyl)porphyrin (3-H2TPyP), Tetra-meso-(4-pyridyl)porphyrin (4-H2TPyP) and [Pt(bipy)Cl2] complex to evaluate its photodynamic properties against Escherichia coli (Gram-negative bacterium) and Staphylococcus aureus (Gram-positive bacterium) microorganisms. For this, the compounds were characterized by elemental analysis, electronic spectroscopy in the UV-vis and infrared regions, as well as their photophysical properties by emission, fluorescence quantum yield and quantum yield of singlet oxygen generation. For the synthesis, it was followed the methodology proposed by Naue and co-workers (2009). In general, the porphyrins showed satisfactory photostability and good quantum yields of singlet oxygen generation values. These characteristics are appreciable under the principles of photodynamic therapy (PDT). Differently from the treatment realized in absence of light, in which the porphyrins were not active against the bacteria culture, in the presence of white light (26 mW cm-2) under the 90 minutes of irradiation, the porphyrins exhibited the satisfactory activity against studied microorganisms, mainly for the tetracationic porphyrins 3-H2TPtPyP and 4-H2TPtPyP, which were seven times more efficient against E. coli and more than three times more effective against S. aureus when compared to their respective precursors. In addition to the effect of the charge, a presence of the PtII complexes potentiated the photodynamic effect of the studied microorganisms when compared with a tetramethylated porphyrin (TMePyP), which is also tetracationic. These better results presented may be related to the cell walls of Gram-negative and Gram-positive bacteria, which are negatively charged due to the presence of phosphate groups and which may facilitate the permeability of porphyrin into the cell. Furthermore, interactions between phosphorus and PtII, obeying the Pearson's theory, may also influence the better assimilation of the tetraplatinated porphyrins into the cell and thus obtain lower minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC).